BIOPOLITIK DAN GERAKAN LITERASI KOMUNIKATIF KAUM MUDA - Faisal, Andi (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
The current demographic bonus is often thought of as a "golden opportunity" for the nation to align itself with other nations. Population growth, especially productive age, will be a key measure in improving the country's productivity. But in the modern Biopolitical Era, it can be a "threat" to the democratic life and public criticism. This paper attempts, critically explores how biopolitical regimes work in controlling the socio-political life of society. Ranging from cultural issues in the post-tradition era, emancipation politics, the digital world, to the social life of public spaces/ spheres, will be the main focus. Alternatively, the idea of youth literacy becomes an offer in reading/ writing various issues of the nation that depart from the roots of everyday life. To cite this article (7th APA style): Faisal, A. (2018). Biopolitik dan Gerakan Literasi Komunikatif Kaum Muda [Biopolitics and the Communicative Literacy Movement of Youth]. Journal Communication Spectrum, 8(1), 72-93. http://dx.doi.org/10.36782/jcs.v8i1.1813